As-spun Bio-novolac Fibre Morphological Study based on Resin’s Physico-chemical Properties - Siti Noorul Aina, Ab Rahim; Sarani, Zakaria; Sharifah Nabihah, Syed Jaafar; Chin, Hua Chia; Rasidi, Roslan; Hatika, Kaco; Sinyee, Gan (Universiti Kebangsaan Malaysia, 2017)
Bio-novolac fibre made from phenol-formaldehyde derived oil palm empty fruit bunch (EFB) was produced using electrospinning method. The bio-novolac phenol-formaldehyde was prepared via liquefaction and resinification at two different molar ratios of formaldehyde to liquefied EFB (LEFB) (F:LEFB = 0.5:1 and 0.8:1). Electrospinning was applied to the bio-novolac phenol-formaldehyde (BPF) in order to form smooth and thin as-spun fibre. The BPF was electrospun at 15 kV and 15 cm distance between needle and collector at a flow rate of 0.5 mL/h. At lower molecular weight of BPF resin, beads formation was observed. The addition of poly(vinyl) butyral (Mw = 175,000 - 250,000) has improved the fibre formation with lesser beads hence produced more fibre. Polymer solution with higher molecular weight produced better quality fibre.